Kesenjangan dalam Wacana Antikorupsi di Indonesia: Temuan dari Literatur Studi Korupsi Kritis - Pertiwi, Kanti (Integritas : Jurnal Antikorupsi, 2019)
Indonesia’s anti-corruption movement has occupied public discourse within the last two decades. Various programs have been carried out by the vanguard in eradicating corruption in this country, the Corruption Eradication Commission (KPK). However, the journey was not free from turbulence and ambiguity, both in the realm of law and in the social sphere. Using a critical discourse analysis approach, this paper examines (anti)corruption discourses in Indonesia and how they are positioned against each other. Previous studies suggest that there is a strong emphasis on universal morality within the dominant discourses on (anti)corruption in Indonesia. Using illustrations which are drawn from in-depth anthropologically-oriented studies, I demonstrate that corruption needs to be understood through the lens of morality-in-context. This further suggests there is a serious gap between the dominant and marginalized discourses of (anti)corruption in Indonesia.